Effect of seed inoculation method with Rhizobium species on the germination of alfalfa seeds (Medicago sativa L.) - Abubaker, Jamal; Mohammed, Nouriya Salah; Essalem, Mohemed; Abdelsalam Abobaker; Massoudah Khalifa (Journal of Pure & Applied Sciences, 2021)
Inoculation alfalfa seeds with the right Rhizobium strain (nitrogen-fixing bacteria) can stimulate root nodulation and improve plant growth and yield. Different inoculation methods are used to inoculate alfalfa seeds; however, the effect of these methods on the germination of seeds is not well documented. In the present study, the germination of alfalfa seeds was evaluated after using different inoculation methods, i.e. Arabic gum solution and glucose solution as adhesive substances on the surface of the seeds, and charcoal powder and sawdust as seeds coating materials. The adhesive solutions and coating materials were tested separately and in combination. Three concentrations of Arabic gum solution and glucose solution were used (i.e., 5, 12.5, and 25%), alongside untreated seeds as control. Germination counts were started on days 3, 4, 6, 8, 10, and 12. On day 12, the experiment ended and the final germination percentage (FGP) and germination index (GI) were calculated. Application of sole Arabic gum and glucose solution of 5 and 12.5% on the surface of the seeds was beneficial to the germination of the inoculated seeds. The application of sole sawdust in the seedbed enhances germination significantly (p < 0.05) compared with coal powder. Moreover, using sawdust as a coating material in combination with Arabic gum (12.5%) gave significantly (p < 0.05) higher germination. The results demonstrate that using 12.5% of adhesive solution either with sawdust or charcoal powder as coating material did not harm the germination of alfalfa seeds.